Geometries, reactivity and binding energy of urea on Mg9O9 - Almeida, Antonio Luiz; Martins, João Batista Lopes (Open Science Journal, 2020)
In this paper we present global and local reactivity results of the urea gas phase molecule and gas phase (MgO)18 agglomerated for understand charge distribution and binding energy (MgO)-UREA. We analyze the quantum chemical descriptors, ionization potential (I), electron affinity (A), chemical hardness (ɳ), chemical potential (μ) and Global Philicity Index (ω) and site reactivity or site selectivity condensed Fukui function analysis of the distribution of atomic charges investigated with methods of Mulliken, Merz-Kolman and Natural Atomic Charges. For instance, the binding energies of MgO-Urea systems are.